KEDUDUKAN LEMBAGA PERKREDITAN DESA (LPD) SEBAGAI SUBJEK HUKUM DALAM MENGAJUKAN PERMOHONAN PAILIT - Ni Putu Ari Setyaningsih (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2021)
LPD is not a microfinance institution that is regulated in Law Number 1 of 2013 concerning Microfinance Institutions because it is excluded under Article 39 paragraph (3) of the law. LPD is not a legal entity like other financial institutions such as banks, rural banks and cooperatives, LPD only has the status as a financial institution belonging to traditional villages until now. In 2016 there was a case of bad loans in one of the LPDs in Bali, namely the Kelan Traditional Village LPD, in this case the settlement was carried out through the bankruptcy mechanism regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (hereinafter referred to as Law No. Bankruptcy Law and PKPU). People who can collect receivables before the court are people (natuurlijke persoon) and legal entities (rechtspersonen). While conceptually LPD is not a microfinance institution as regulated in the Law on Microfinance Institutions and LPD is a financial institution that is not a legal entity such as banks, rural banks and cooperatives. Normative legal research is carried out by library research by tracing secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials, with documentation methods and tools in the form of document studies. Data analysis used qualitative analysis. Based on the results of research and discussion, it shows that legal subjects in bankruptcy are legal subjects that are recognized in civil law, namely individuals and legal entities because Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations is a special regulation of Article 1131 and Article 1132 of the Law. - Civil Law Law, so that LPD which is a customary institution that does not meet the requirements as a legal entity is not a legal subject that can file an application for bankruptcy.